The organization of ancient economies a global perspective - Hirth, Kenneth 1949- (Cambridge University Press, 2020)
"In this book, Kenneth Hirth provides a comparative view of the organization of ancient and premodern society and economy. Hirth establishes that humans adapted to their environments, not as individuals but in the social groups where they lived and worked out the details of their livelihoods. He explores the variation in economic organization used by simple and complex societies to procure, produce, and distribute resources required by both individual households and the social and political institutions that they supported. Drawing on a wealth of archaeological, historic, and ethnographic information, he develops and applies an analytical framework for studying ancient societies that range from the hunting and gathering groups of native North America, to the large state societies of both the New and Old Worlds. Hirth demonstrates that despite differences in transportation and communication technologies, the economic organization of ancient and modern societies are not as different as we sometimes think."
Includes bibliographical references and index
Keywords: Wirtschaft; Antike; Wirtschaftsgeschichte / (DE-627)091400961 / (DE-STW)15706-6; Wirtschaftsordnung / (DE-627)091401119 / (DE-STW)11068-4; Altertum / (DE-627)091346754 / (DE-STW)15689-1; Economic history